2023
DOI: 10.3389/fpsyg.2023.1231920
|View full text |Cite
|
Sign up to set email alerts
|

Parenting style and children emotion management skills among Chinese children aged 3–6: the chain mediation effect of self-control and peer interactions

Dexian Li,
Wencan Li,
Xingchen Zhu

Abstract: Drawing on ecosystem theory, which is based on the interaction of family environment, individual characteristics, and social adaptation, this study aimed to examine the effects of parenting style on emotion management skills and the mediating roles of self-control and peer interactions among Chinese children aged 3–6 years. Some studies have investigated the relationship between parenting style and emotion management skills. However, research on the underlying mechanisms is still deficient. A sample of 2,303 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 178 publications
1
1
0
Order By: Relevance
“…Similar to the framing of the stress and coping theory (Lazarus & Folkman, 1984), having more concerns related to stressful circumstances was related to increased MPD. This is in line with the findings showing that when mothers perceive the situation as more controllable, their children show less negative mental health symptoms, highlighting the importance of emotional coping skills for parents (Li et al, 2023). Recognizing this direct link highlights the importance of cultivating effective emotion coping skills for parents.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the framing of the stress and coping theory (Lazarus & Folkman, 1984), having more concerns related to stressful circumstances was related to increased MPD. This is in line with the findings showing that when mothers perceive the situation as more controllable, their children show less negative mental health symptoms, highlighting the importance of emotional coping skills for parents (Li et al, 2023). Recognizing this direct link highlights the importance of cultivating effective emotion coping skills for parents.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, authoritarian parenting has been found to have a detrimental impact on children's emotional management abilities. 50 Furthermore, among college students, parenting styles may also influence their emotional management and responses when confronted with stressful life events, subsequently either promoting or weakening the occurrence of depressive symptoms. Secondly, in terms of self-esteem and self-confidence, research has shown a significant correlation between parenting styles and adolescent self-esteem.…”
mentioning
confidence: 99%